Determination of Appropriate Rate and Mode of Lime Application on Acid Soils of Western Kenya: Targeting Small Scale Farmers - C. K , Serrem; J. K. , Kiplagat; J. R. , Okalebo; . D. S, Mbakaya; B. , Jama (African Journal of Education,Science and Technology (AJEST), 2015)
Western Kenya is experiencing a decline in food production due to increased soil acidity. There is the potential of using agricultural lime, inorganic fertilizers, and Minjingu rock phosphates to address soil acidity problem while promoting food production. Use of lime is still low among smallholder farmers due to lack of awareness on its effectiveness, and the best mode of application. This study aimed at comparing performance of maize under three methods of lime application (spot, band, and broadcast methods) and four rates of application (0, 2, 4, and 6 t/ha), conducted in two districts, Ugenya and Kakamega North of Western Kenya. The on-farm experiment was laid out in a 3 ´ 4 factorial in a randomized complete block design (RCBD) with four replications. All treatments received a blanket application of phosphorus (as TSP) and nitrogen (as CAN) at the rate of 26 kg/ha P and 75 kg/ha N, respectively. There was increase in grain yield with lime application in both districts. Use of any of the methods gave differences in yield between lime rates used. In overall yield, broadcast method was highest in the two district whereas the best rate was using 6 t/ha, due to high lime to soil contact. Application of 6 t/ha of lime by the spot method decreased yield compared to the other method using the same rate due to overliming effects like scorching of seedlings, effects on soil structure, and element toxicities and deficiencies. This was not observed in North Kakamega because of differences in lime requirements of the two districts. Labor required for the application of lime differed with method. Broadcast method was costly because a farmer was required to incorporate lime in the entire plot, while for the other methods, only the applied areas (band rows and hills) are tilled. The broadcast method is expensive due to lime application but gave the best yield response.